Strategi Komunikasi DPMPTSP Kabupaten Serang dalam Peningkatan Kualitas Pelayanan Perizinan Melalui OSS - Nida Silvia Lestari; Titi Stiawati; Ipah Ema Jumiati; Arenawati Arenawati (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2023)
The purpose of this study is to learn more about the various communication strategies used by the Serang Regency Investment and One-Stop Service Office (DPMPTSP), through this the government increases permission for people to do certain things, so that this will make life easier. easy for many people. This study uses a qualitative approach that relies on descriptive data collection techniques, such as observation and interviews. This research gives the result that the strategy used is to build communication through internal and external approaches. Internal approach communication is carried out by building emotional closeness to each individual who works within the Investment and One-Stop Service Office of Serang Regency, so that it can produce cooperation with good output in providing services to the community. As for the external approach communication strategy, namely carrying out a communication strategy that aims to create excellent public services through innovation in non-business licensing services and business licensing. The implementation of the non-business licensing system is carried out through the SIMPONIE Wabsite (Online Licensing Management Information System) as a non-business licensing service facility that is not processed through the OSS (Online Single Submission) system, to simplify and speed up business licensing for business actors. Through the OSS (Online Single Submission) service in collaboration with the regional government, namely the Serang Regency One-Stop Investment and Integrated Services Service to socialize and assist with problems for business actors in their area.